Strengthening Character Education for Gen Z ‎ in the Era of Disruption through a Personal-Constructive Sufi Approach - Saiful Islam,; Fauzi Muharom,; Fauzi Annur,; Arsyil Azwar Senja,; Kunti Zahrotun Alfi, (TADRIS: Jurnal Pendidikan Islam, 2022)
This study aims to find out how educational institutions prepare strategies and concepts for their students in the current era of disruption, especially in strengthening character formation in Generation Z. An era that offers acceleration in various areas of life, one of them is acceleration in uprooting the established foundations of life. The research method used in this research is library research with an analytical descriptive approach. The results of this study are that education must be able to present linear strategies and concepts with the characteristics of the Z-generation. One of these concepts is through a personal-constructive approach in strengthening the character education of students, especially the Z-generation. This approach was carried out as the Sufis in ancient times tried to improve their morals in totality before God and humans, namely through self-awareness of their spiritual potential and concrete actions that focused on fundamental things such as repentance, patience, sincerity, etc.